Indian theologies : in search of methods and models for theologizing - Jayanth, Mathew (ed.) (New Delhi, Christian World Imprints & Jnana-Deepa Vidyapeeth, 2017)
Contributed articles presented at Seminar on Indian Theological Methods, held at Jnana-Deepa Vidyapeeth in 2010
Keywords: Catholic Church.-- India; Conference papers and proceedings; Theology.-- Methodology; Theology, Doctrinal.-- India.-- Congresses